Diversification or distortion? The role of ETFs in retail investor portfolios and performance - Wu, Zheng; Westerholm, P. Joakim; Wang, Zhen (Journal of Financial Stability, 2026)
We examine how ETF adoption affects retail investor performance using a comprehensive panel of 524,181 Finnish investors tracked from 2007 to 2022. ETF adopters tend to be older, predominantly male, and more active, holding smaller but better-diversified portfolios. Importantly, first-time use of ETFs yields statistically significant improvements in risk-adjusted returns. ETF users also demonstrate greater portfolio resilience during financial crises. Our findings confirm that ETFs serve as effective tools for enhancing performance and managing risk for retail investors.